Analisis Evaluasi Program Pendidikan Dalam Pembelajaran Di Sekolah - Alfie Ridho; Arina Denggan Munthe; Dimas Andika Shaputra; Indah Wahyuni; Lutfhia Farhana Putri Lubis; Nursiti Maysarah; Inom Nasution (Lembaga Pengembangan Kinerja Dosen, 2023)
This paper discusses the evaluation of educational programs in learning in schools where the implementation of education as part of educating the life of the nation must receive full attention from policy makers in this country, as stated in article 31 of the 1945 Constitution, amendment 4 that every citizen country has the right to education. The main goal of education is to develop human beings from an intellectual, emotional and spiritual perspective. In terms of its objectives, the output of education should be able to produce human resources who have advantages in terms of intellectual, emotional and spiritual. Education must be able to answer the challenges of the development of science and technology which is accompanied by a flow of information that is increasingly developing rapidly. The writing of this article uses the method of literature analysis (library research), namely the study of various scientific sources such as articles in both national and international journals and books that are in accordance with the themes and titles discussed. The literature analysis method makes the writer to read and find sources of reading material that are appropriate to the themes being discussed or are relevant. In this case the method of literature analysis is an appropriate and effective step.